Taxonomic composition, abundance and habitat associations of squid paralarvae in the northern Gulf of Mexico. (August 2021) - Sluis, Michelle Zapp; Judkins, Heather; Dance, Michael A.; Vecchione, Michael; Cornic, Maëlle; Sutton, Tracey; Rooker, Jay R.
Abstract: Summer plankton surveys were conducted in 2015–2017 to characterize the distribution and abundance of squid paralarvae in epipelagic waters of the northern Gulf of Mexico (Gulf). Paralarvae present at stations sampled were from 12 families, with the most abundant being Ommastrephidae (flying squids), Enoploteuthidae (armed squids) and Onychoteuthidae (hooked squids). Mean density and percent frequency of occurrence for squid paralarvae across all surveys was 8.8 paralarvae 1000 m −3 and 76%, respectively. Julian day, salinity, sea surface height (SSH) and time of day were identified as influential environmental variables in generalized additive models (GAMs). Paralarval densities peaked during early morning and late evening sampling times, which is in accord with diel vertical migration patterns. Densities increased in early July, in areas with low SSH and lower salinity (28–35 psu), indicating upwelling areas and proximity to inflow from the Mississippi River represent productive early life habitats for squid. Results suggest that oceanic squid spawn in the northern Gulf in the summer exploiting the position of mesoscale oceanographic features and the extension of freshwater discharges from the Mississippi River. Highlights: Upwelling areas and river discharge create productive habitat for squid paralarvae. Preference for summer hatching in the northern Gulf of Mexico. Main paralarvae families are Ommastrephidae, Enoploteuthidae and Onychoteuthidae. Squid paralarvae exhibit diel vertical migration patterns.